SOSIALISASI EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) UNTUK KELOMPOK RENTAN DI MEUNASAH GAMPONG SEUMEUREUNG KABUPATEN ACEH BESAR - Muharrina, Cut Rahmi; Yarah, Saufa; Wahyuni, Srie; Laina, Bilqis; Lysabena (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Clean and Healthy Living Behavior is basically an effort to transmit experiences regarding healthy living behavior through individuals, groups or the wider community using communication channels as a medium for sharing information. There is various information that can be shared, such as educational material to increase knowledge and improve attitudes and behavior regarding a clean and healthy way of life. Clean and Healthy Living Behavior is a social engineering that aims to make as many members of society as possible agents of change in order to be able to improve the quality of daily behavior with the aim of living a clean and healthy life. Vulnerable groups are those who have vulnerabilities and experience physical, mental and social limitations so that they are unable to access basic services and need special assistance from the state or other communities. Vulnerable groups can also be defined as groups or communities that are at risk of experiencing poor health problems. Generally because they cannot achieve social, economic and environmental access.